Non‐uniform Self‐folding of Helical Poly(fluorenevinylene) Derivatives in the Solid State Leading to Amplified Circular Dichroism and Circularly Polarized Light Emission. Issue 43 (27th September 2022) - Wu, Pengfei; Pietropaolo, Adriana; Fortino, Mariagrazia; Shimoda, Shuhei; Maeda, Katsuhiro; Nishimura, Tatsuya; Bando, Masayoshi; Naga, Naofumi; Nakano, Tamaki
Abstract: An unprecedented non‐uniform self‐folding of artificial polymer chains composed of turn moieties and stretched segments is presented through the design of a set of optically active poly(fluorene‐2, 7‐diylethene‐1, 2‐diyl) (poly(fluorenevinylene)) derivatives bearing a neomenthyl group and a pentyl group attached at the 9‐position of fluorene backbone at various ratios. The folded structure is formed and stabilized through inter‐chain interactions in the solid state, leading to remarkably enhanced chiroptical properties (chirality amplification) in terms of circular dichroism (CD) and circularly polarized light (CPL) emission. This phenomenon is rationalized by experimental and theoretical CD and CPL spectral analyses. The polymer arrangements in the solid state were further assessed through transmission electron microscopic observations combined with enhanced sampling molecular dynamics simulations in the solid state revealing the thin film organizations. Abstract : Optically active poly(fluorenevinylene) derivatives self‐fold in the solid state into a non‐uniform structure with sharp turns connecting stretched segments where the turns exhibit remarkable optical anisotropy in the ground state and in excited states.